2016
DOI: 10.1002/cphc.201600633
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Transitions in Conformationally Controlled Peralkylated Hexasilanes

Abstract: The photophysical properties of oligosilanes show unique conformational dependence due to σ-electron delocalization. The excited states of the SAS, AAS, and AEA conformations of peralkylated n-hexasilanes, in which the SiSiSiSi dihedral angles are controlled into a syn (S), anti (A), or eclipsed (E) conformation, were investigated by using UV absorption, magnetic circular dichroism (MCD), and linear dichroism spectroscopy. Simultaneous Gaussian fitting of all three spectra identified a minimal set of transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 94 publications
1
22
0
Order By: Relevance
“…In peralkylated n ‐tetrasilanes, the spectra of which have been studied in considerable detail in a series of conformations, these additional transitions have been uncovered and are in impressive agreement with the results of TD‐DFT/TZ, CAS‐PT2, and SAC‐CI calculations . A less detailed study is available for a few conformers of peralkylated hexasilanes …”
Section: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In peralkylated n ‐tetrasilanes, the spectra of which have been studied in considerable detail in a series of conformations, these additional transitions have been uncovered and are in impressive agreement with the results of TD‐DFT/TZ, CAS‐PT2, and SAC‐CI calculations . A less detailed study is available for a few conformers of peralkylated hexasilanes …”
Section: Methods and Resultsmentioning
confidence: 99%
“…Figure shows that the computations reproduce the behavior of the energy and the intensity of the first observed absorption maximum in samples with random sense of helicity quite well. It is also known that they perform well for the weak transitions in Si 3 Me 8 and a few tetrasilanes and hexasilanes, and it is reasonable to assume that the TD‐DFT B3LYP/TZ level of computation also describes the regular helical conformers correctly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B3LYP/6-311G(d) was selected to allow for comparison to the literature, as Michl et al reported analysis of linear alkylsilanes with this basis set and functional. 46 Significant changes were not observed at higher levels of theory. Good agreement was observed between calculated and experimental HOMO energies (Figure 3a, compare the solid and dashed lines).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…B3LYP/6-311G­(d) was selected to allow for comparison to the literature, as Michl et al. reported analysis of linear alkylsilanes with this basis set and functional . Significant changes were not observed at higher levels of theory.…”
Section: Results and Discussionmentioning
confidence: 99%